The Dual Role of the Glycolipid Envelope in Different Cell Types of the Multicellular Cyanobacterium Anabaena variabilis ATCC 29413 - Garg, Ritu; Maldener, Iris (Frontiers in Microbiology, 2021)
Anabaena variabilis is a filamentous cyanobacterium that is capable to differentiate specialized cells, the heterocysts and akinetes, to survive under different stress conditions. Under nitrogen limited condition, heterocysts provide the filament with nitrogen by fixing N2. Akinetes are spore-like dormant cells that allow survival during adverse environmental conditions. Both cell types are characterized by the presence of a thick multilayered envelope, including a glycolipid layer. While in the heterocyst this glycolipid layer is required for the maintenance of a microoxic environment and nitrogen fixation, its function in akinetes is completely unknown. Therefore, we constructed a mutant deficient in glycolipid synthesis and investigated the performance of heterocysts and akinetes in that mutant strain. We chose to delete the gene Ava_2595, which is homologue to the known hglB gene, encoding a putative polyketide synthase previously shown to be involved in heterocyst glycolipid synthesis in Anabaena PCC 7120, a species which does not form akinetes. Under the respective conditions, the Ava_2595 null mutant strain formed aberrant heterocysts and akinete-like cells, in which the specific glycolipid layers were absent. This confirmed firstly that both cell types use a glycolipid of identical chemical composition in their special envelopes and, secondly, that HglB is essential for glycolipid synthesis in both types of differentiated cells. As a consequence, the mutant was not able to fix N2 and to grow under diazotrophic conditions. Furthermore, the akinetes lacking the glycolipids showed a severely reduced tolerance to stress conditions, but could germinate normally under standard conditions. This demonstrates the importance of the glycolipid layer for the ability of akinetes as spore-like dormant cells to withstand freezing, desiccation, oxidative stress and attack by lytic enzymes. Our study established the dual role of the glycolipid layer in fulfilling different functions in the evolutionary-related specialized cells of cyanobacteria. It also indicates the existence of a common pathway involving HglB for the synthesis of glycolipids in heterocysts and akinetes.